2014
DOI: 10.1037/a0037817
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time of night on wake–dream continuity.

Abstract: Research has demonstrated a number of time of night and stage of sleep differences in dream content, such as that dreams from later in the night are longer, more emotional, and more bizarre. It was hypothesised that time of night may therefore demonstrate differences in the continuity of waking life into dreams. Participants (N=16) were systematically awoken four times a night for two nights and rated their dreams for wake-dream continuity on a number of dimensions. It was found that time of night affects wake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…We also observed a trend for future-oriented dreams to become proportionally more common later in the night, as participants move toward morning waking. This echoes a small-sample study by Malinowski & Horton [ 55 ], which observed a non-significant but substantially sized increase in participant-rated similarity of dreams to future events across the night. In a subsequent study, the same authors also reported that late in the night, participant ratings of recent-memory incorporation were correlated with their ratings of future-event incorporation [ 56 ].…”
Section: Discussionsupporting
confidence: 83%
“…We also observed a trend for future-oriented dreams to become proportionally more common later in the night, as participants move toward morning waking. This echoes a small-sample study by Malinowski & Horton [ 55 ], which observed a non-significant but substantially sized increase in participant-rated similarity of dreams to future events across the night. In a subsequent study, the same authors also reported that late in the night, participant ratings of recent-memory incorporation were correlated with their ratings of future-event incorporation [ 56 ].…”
Section: Discussionsupporting
confidence: 83%
“…In this study, all dreams were collected at home without controlling for the time of night when participants’ dreams occurred. The lack of control may lead to potential errors, as evidence suggests that waking-life elements are represented with different frequencies from the early to the late night, and late-night dreams are more bizarre (Malinowski & Horton, 2014c). The bizarreness of dreams may affect participants’ ratings for the incorporation of waking-life experiences into dreams.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies included codings for aggressive and friendly interactions, but aggression and friendliness are not among the five to seven basic emotions that are generally agreed upon by research psychologists (e.g., anger, apprehension/fear, sadness, disgust/contempt, surprise, love, and joy; e.g., Ekman, 1992, 2016; Shaver, Schwartz, Kirson, & O’Connor, 1987). On the basis of these points, it can be seen that any emphasis on the incorporation of waking emotional experiences into dreams is an offshoot of Schredl’s (2006, 2012) experiential incorporation hypothesis, which could be called the emotion assimilation hypothesis to distinguish it from the continuity hypothesis (e.g., Malinowski & Horton, 2014, 2016; Schredl, 2006; van Rijn, Eichenlaub, & Blagrove, 2016).…”
Section: Looking For Continuity In All Of the Wrong Placesmentioning
confidence: 99%